2018
DOI: 10.35790/jbm.10.2.2018.20086
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Nilai Carcinoembryonic Antigen dengan Derajat Diferensiasi pada Karsinoma Kolorektal di RSUP Prof. Dr. R. D. Kandou Manado

Abstract: Colorectal cancer is a serious health problem in Indonesia as well as in North Sulawesi. Serum carcinoembryonic antigen (CEA) is a progmostic factor in patients with this disease. This study was aimed to obtain the correlation between the histopathological differentiation stage and serum CEA level in colorectal cancer patients at Prof. Dr. R. D. Kandou Hospital Manado. This was an analytical correlation study. Subjects were colorectal cancer patients who had preoperative serum CEA level and histopathological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
1
0
0
Order By: Relevance
“…That it can be concluded that there are differences in the CEA level based on the histopathological grade. This result is similar to a study by Wesley et al 16 (p<0.0001).…”
Section: Discussionsupporting
confidence: 93%
“…That it can be concluded that there are differences in the CEA level based on the histopathological grade. This result is similar to a study by Wesley et al 16 (p<0.0001).…”
Section: Discussionsupporting
confidence: 93%